Ethical Issues and Professional Functionalism of Counseling in the 21st Century - J., EBUTE,; G. E., ATTAH,; A., HARUNA, (International Journal on Integrated Education, 2023)
Ethics of every profession is the rule of which the profession plays. Till today ethics of counselling is the building blocks of counselling and the guiding tracks in the un/b/ding complicated and interconnected global space where technology has made change a constant in life style. Counselling practice is guided by code of’ ethics and standards which provide a common base for the application and interpretation of assessment and evaluation tools in counselling work. A common thread running through all the codes of ethical standards is ethical requirements which call on practitioners to observe some common theme of values and principles in the delivery of counselling services. But beyond the documented standards and guides are the mores and conventions which though have no legal and enforceable powers, farm the basis of resolution of ethical issues in counselling. These foundational issues are values, principles and ethical traits for effective functionalism of counselling in this era of technological, cultural and behavioural dynamism. Thus, the paper tends to develop a framework on ethical issues and professional counseling, while some contemporary and evolving ethical issues like culture, law, morality, counselor-client confidentiality, rights of minors, education and training which impacts on counseling work will be discussed. With the aim of creating solution to the dilemma that negates the professionalism of counseling in the 21st century.